High-entropy doped lithium cobalt oxide positive electrode material as well as preparation method and application thereof

Through high -entropy doping technology, doped TI, MG, AL, ND (PR) elements to form a cobalt -lithium cobaltate positive pole material with surface integrated layers and body phase doped, solving lithium cobaltate's circulating performance attenuation and attenuation at high voltage at high voltage The problem of unstable surface interface realizes the improvement of battery cycle stability and electrochemical properties.

CN119361680APending Publication Date: 2025-01-24GUANGDONG UNIV OF TECH +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411409817.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-10
Publication Date
2025-01-24

AI Technical Summary

Technical Problem

Lithium cobalt oxide (LCO) has problems such as cycling performance attenuation, low actual specific capacity and unstable surface interface under high voltage conditions. Especially at 4.5V or above, the interface side reaction between the cathode and the electrolyte is severe, resulting in high impedance. The formation of the interface layer and the instability of the material.

Method used

Through high-entropy doping technology, Ti, Mg, Al, Nd (Pr) is used to dope co-modified lithium cobalt oxide to form a structure of surface integrated layer and bulk doping, which enhances the stability of the layered structure of the material and extracts more It has multiple lithium ions and improves the stability of the material surface and interface, thereby improving the cycle stability under high voltage conditions.

Benefits of technology

The cycle stability of lithium cobaltate orthopedic materials is improved under high voltage, which extends the cycle life of the battery and improves the electrochemical performance, including the power supply capacity, the first efficiency and capacity maintenance rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119361680A_ABST
    Figure CN119361680A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium cobalt oxide positive electrodes, and discloses a high-entropy doped lithium cobalt oxide positive electrode material as well as a preparation method and application thereof. The molecular formula of the high-entropy doped lithium cobalt oxide positive electrode material is LiCo (1-y) MgxAlyPrzTi (0.0025) O2 or LiCo (1-y) MgxAlyNdzTi (0.0025) O2, x is greater than or equal to 0.001 and less than or equal to 0.01, y is greater than or equal to 0.001 and less than or equal to 0.01, and z is greater than or equal to 0.001 and less than or equal to 0.01. The high-entropy doped lithium cobalt oxide positive electrode material disclosed by the invention is formed by combining a surface integration layer and bulk phase doping, so that irreversible transformation of a material structure from an O3 phase to an O1-O3 blended phase (H1-3) is inhibited, and slippage of a transition metal layer and collapse and irreversible phase transformation of an O3 lattice structure are prevented; the stability of a surface interface and a bulk phase structure of the lithium cobalt oxide positive electrode material under high voltage is improved, and the lithium cobalt oxide positive electrode material can be applied to a lithium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium cobalt oxide positive electrodes, and in particular relates to a high-entropy doped lithium cobalt oxide positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries are by far the most promising energy storage devices due to their high operating voltage, high specific energy, long cycle life, low self-discharge, no memory effect, and environmental protection. They are widely used in digital products, hybrid electric vehicles (HEVs), and pure electric vehicles (VEs). The performance of lithium-ion batteries depends largely on the cathode material.

[0003] Lithium cobalt oxide (LCO) is the earliest commercialized lithium-ion battery cathode material with a compaction density of 4.2g / cm 3 , with a volume capacity of up to 3724Wh / L, it occupies a dominant position in the field of 3C portable electronic devices. The research and development of high-voltage LCO meets the market demand for long-lasting portable electronic devices. The theoretical specific capacity of LCO is 274mAh / g. Since the current cut-off voltage is generally below 4.45V, its actual specific capacity is only 175mAh / g. If it can achieve stable operation at a high voltage of 4.6V, the specific capacity can be increased to 220mAh / g. However, when the charging voltage is too high, the following problems will occur: (1) Cycle performance degradation: At high voltage, Co 4+ It is easily soluble in the electrolyte, accelerating the decomposition of the electrolyte; (2) Low actual specific capacity: When LCO is highly de-lithiated during charging at high voltage, an irreversible phase transition from O3 hexagonal phase to H1-3 hexagonal phase occurs, internal strain accumulation leads to crack formation and particle crushing, and oxygen loss leads to phase change structure collapse; (3) Above 4.5V, the interface side reaction between the cathode and the electrolyte is particularly serious, and the byproducts accumulate to form a high-impedance interface layer, among which the corrosive byproducts destroy the stability of the LCO surface, causing surface interface instability. In response to the problems of LCO, there have been many studies to improve the high-voltage performance of LCO from the aspects of element doping, surface coating, and electrolyte optimization. Summary of the invention

[0004] Based on the problems existing in the background technology, in order to solve the above-mentioned shortcomings and deficiencies, the present invention provides a high-entropy doped lithium cobalt oxide positive electrode material, which is Ti, Mg, Al, and Nd (Pr) doped co-modified lithium cobalt oxide, and the Ti, Mg, Al, and Nd (Pr) surface integrated layer is doped with the bulk phase to enhance the layered structure stability of lithium cobalt oxide, extract more lithium ions, and improve the surface interface stability of the material to improve the cycle stability of lithium cobalt oxide under high voltage conditions.

[0005] Another object of the present invention is to provide a method for preparing the above-mentioned high entropy doped lithium cobalt oxide positive electrode material.

[0006] Another object of the present invention is to provide an application of the above-mentioned high entropy doped lithium cobalt oxide positive electrode material.

[0007] The purpose of the present invention is achieved through the following technical solutions:

[0008] A high entropy doped lithium cobalt oxide cathode material has the molecular formula LiCo (1-y) Mg x Al y Pr z Ti 0.0025 O2 or LiCo (1-y) Mg x Al y Nd z Ti 0.0025 O2, where 0.001≤x≤0.01, 0.001≤y≤0.01, 0.001≤z≤0.01.

[0009] The method for preparing the high entropy doped lithium cobalt oxide positive electrode material comprises the following steps:

[0010] S1. A lithium compound, a cobalt compound, a titanium compound, a magnesium compound, an aluminum compound, a neodymium compound or a praseodymium compound is placed in a ball mill and ground to obtain a mixed powder;

[0011] S2. The mixed powder is heated to 800-1200° C. in an atmosphere of air or oxygen and sintered. After cooling to room temperature, the mixed powder is heated to 800-1200° C. and sintered again to obtain high-entropy doped lithium cobalt oxide.

[0012] Preferably, in step S1, the lithium compound is one or more of lithium hydroxide, lithium carbonate or lithium acetate; the cobalt compound is one or more of cobalt trioxide, cobalt sulfate or cobalt nitrate; the titanium compound is tetrabutyl titanate and / or titanium oxide; the magnesium compound is one or more of magnesium nitrate, magnesium oxide, magnesium sulfate or magnesium chloride; the aluminum compound is one or more of aluminum sulfate, aluminum oxide, aluminum acetate or aluminum fluoride; the neodymium compound is neodymium oxide and / or neodymium nitrate, and the praseodymium compound is praseodymium oxide and / or praseodymium nitrate.

[0013] Preferably, the added amount of the titanium compound, magnesium compound, aluminum compound, neodymium compound or praseodymium compound in step S1 is 0.1-1 mol % of the high entropy doped lithium cobalt oxide positive electrode material respectively.

[0014] Preferably, in step S1, the molar ratio of Li in the lithium compound to Co in the cobalt compound is (1-x):(1-y), 0≤x≤0.1, 0≤y≤0.1.

[0015] Preferably, the grinding speed in step S1 is 400-1000 rpm, and the grinding time is 10-20 h.

[0016] Preferably, the heating rate in step S2 is 1-5° C. / min, the first sintering time is 10-20 h, and the second sintering time is 5-10 h.

[0017] Application of the high entropy doped lithium cobalt oxide positive electrode material in lithium batteries.

[0018] A high entropy doped lithium cobalt oxide positive electrode material is prepared by the method.

[0019] The present invention can effectively prevent direct contact between the positive electrode and the electrolyte by constructing a surface integrated layer, but it is difficult to delay the gradual penetration of the structural evolution from the surface to the bulk phase; and doping forms a high entropy zone near the surface, including an inherent thin disordered rock salt shell and a segregated surface of the dopant. High entropy complexes can effectively inhibit oxygen evolution and deconstruction of near-surface structures. The reversibility of the phase change between O3 and H1-3 and the thermal stability of the cathode are also greatly improved. At the same time, the problems of oxygen evolution, electrolyte decomposition and irreversible phase change under high voltage conditions are solved, achieving a significant improvement in electrochemical performance.

[0020] The modified LCO particles of the present invention are composed of an outer surface integrated layer, a bulk doped transition layer and a lithium cobalt oxide matrix from the outside to the inside; wherein the outer surface integrated layer is a Ti-based integrated layer, the bulk doped transition layer is a spinel-like transition layer gradiently doped with Mg, Al, Nd (Pr) and Ti elements, and the lithium cobalt oxide matrix is ​​an unmodified layered bulk phase. The combination of the surface integrated layer and bulk doping of the high entropy doped lithium cobalt oxide positive electrode material inhibits the irreversible transformation of the material structure from the O3 phase to the O1-O3 mixed phase (H1-3), prevents the slip of the transition metal layer and the collapse and irreversible phase transformation of the O3 lattice structure, and improves the stability of the surface interface and bulk structure of the LCO positive electrode material under high voltage. The Li-metal mixed structure in the surface integration layer can inhibit the release of lattice oxygen, reduce the deconstruction of the surface structure under high voltage, and improve the interface stability of the positive electrode-electrolyte; at the same time, surface integration can improve the ionic conductivity and reduce the lithium ion diffusion barrier energy, thereby improving the rate performance of the material. The dual-site doping of bulk Li and transition metal sites can improve the structural stability of the supporting layered structure and enhance the electrochemical performance of ion conductivity. At the same time, the synergistic or offsetting effects between the four doping elements can be utilized. Reasonable design can further improve the battery capacity and cycle stability.

[0021] Compared with the prior art, the present invention has the following beneficial effects:

[0022] 1. The present invention uses Al-doped LiCoO2 material to expand the interlayer spacing and reduce Li + The diffusion barrier increases the Li+ The diffusion coefficient is increased, which improves the charge and discharge rate; the doping of Mg and Nd (Pr) can be evenly distributed in the lattice, and their good stacking order is conducive to the reduction of charge transfer resistance; the surface integration layer and body doping of Ti can effectively inhibit the oxidation activity of oxygen ions to slow down the side reactions between the material and the electrolyte under high voltage, ensuring that the modified LCO has excellent electrochemical properties.

[0023] 2. The combination of the surface integration layer and bulk doping of the present invention inhibits the irreversible transformation of the material structure from the O3 phase to the O1-O3 mixed phase (H1-3), prevents the slip of the transition metal layer and the collapse and irreversible phase transformation of the O3 lattice structure, and improves the stability of the surface interface and bulk structure of the LCO positive electrode material under high voltage. Among them, the Li-metal mixed structure in the surface integration layer can inhibit the release of lattice oxygen, reduce the deconstruction of the surface structure under high voltage, and improve the interface stability of the positive electrode-electrolyte; at the same time, surface integration can improve ionic conductivity and reduce the lithium ion diffusion barrier energy, thereby improving the rate performance of the material. The dual-site doping of the bulk Li site and the transition metal site can further improve the battery capacity and cycle stability by utilizing the synergistic or offsetting effect between the two doping elements while supporting the layered structure to improve the structural stability and the electrochemical performance of the ionic conductivity.

[0024] 3. The surface integrated layer and bulk high entropy doped lithium cobalt oxide positive electrode material prepared by the present invention were assembled into a conventional button half-cell and the electrochemical performance was tested. The maximum value reached 211.06 mAh g at 3-4.6 V and 1 C. -1 After 100 cycles, there is still 173.97 mAhg -1 And 82.43% capacity retention rate, 200 times still has 147.74mAhg -1 The discharge specific capacity and capacity retention rate of 70% are achieved.

[0025] 4. The present invention adopts a one-pot method to ball-mill a certain amount of lithium cobalt oxide powder, cobalt oxide powder, titanium-containing material, neodymium-containing material, magnesium-containing material, and aluminum-containing material, and then sinter at high temperature and perform secondary annealing. Then, an outer surface titanium-based integrated layer is constructed from the outside to the inside on the LCO surface layer, and a near-surface bulk phase titanium, neodymium (praseodymium), magnesium, and aluminum element gradient doping transition layer is constructed. This method establishes a dual protection mechanism for the surface interface and the bulk phase, and simultaneously constructs a surface integrated structure and a dual-position doping of the bulk phase (Li position and transition metal position), which is an effective way to enhance the cycle stability of LCO positive electrode materials under high voltage.

[0026] 5. The raw materials used in the present invention are low-cost and easy to obtain, and only a ball mill is used for doping treatment. The method for preparing the modified lithium cobalt oxide positive electrode material is simple and stable, which creates good conditions for the industrial application of this technology. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 XRD spectra of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1.

[0028] Figure 2 The discharge specific capacity cycle of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1 under the conditions of 1C (200 mA / g) and 4.6V cut-off voltage.

[0029] Figure 3 It is the first coulombic efficiency of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1 under the conditions of 1C (200mA / g) and 4.6V cut-off voltage. DETAILED DESCRIPTION

[0030] The content of the present invention is further described below in conjunction with specific examples, but it should not be construed as limiting the present invention. If not specifically indicated, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0031] Example 1

[0032] 1. Add Li2CO3, Co3O4, MgO, Al2O3, Nd2O3, and TiO2 (the molar ratio of Li:Co:Mg:Al:Nd:Ti is 1.040:0.995:0.005:0.005:0.005:0.0025) into a ball mill and mill at 450 rpm for 12 h to mix them evenly to obtain a mixed powder;

[0033] 2. The mixed powder was placed in a muffle furnace, heated to 1000°C at 2°C / min and sintered for 12 hours. After cooling, it was added to an agate bowl and ground again. The mixture was heated to 900°C at 2°C / min and sintered for 6 hours. After cooling to room temperature, a high entropy doped lithium cobalt oxide positive electrode material was obtained. Its molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Nd 0.0025 O2.

[0034] Example 2

[0035] The difference from Example 1 is that the Nd2O3 in step 1 is replaced by Pr6O 11 , a high entropy lithium cobalt oxide cathode material is obtained, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0036] Example 3

[0037] The difference from Example 1 is that the molar ratio of Li:Co:Mg:Al:Nd:Ti in step 1 is 1.035:0.9925:0.0075:0.0075:0.0075:0.0025, and the high entropy doped lithium cobalt oxide positive electrode material is prepared, and its molecular formula is LiCo 0.9925 Mg 0.0075 Al 0.0075 Nd 0.0075 Ti 0.0025 O2.

[0038] Example 4

[0039] The difference from Example 1 is that the molar ratio of Li:Co:Mg:Al:Nd:Ti in step 1 is 1.045:0.9975:0.0025:0.0025:0.0025:0.0025, and the high entropy doped lithium cobalt oxide positive electrode material is prepared, and its molecular formula is LiCo 0.9975 Mg 0.0025 Al 0.0025 Pr 0.0025 Ti 0.0025 O2.

[0040] Example 5

[0041] The difference from Example 1 is that the MgO in step 1 is replaced by Mg(NO3)2 to obtain a high entropy doped lithium cobalt oxide positive electrode material, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0042] Example 6

[0043] The difference from Example 1 is that the Al2O3 in step 1 is replaced by Al(NO3)3·9H2O to obtain a high entropy doped lithium cobalt oxide positive electrode material, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0044] Example 7

[0045] The difference from Example 1 is that the Nd2O3 in step 1 is replaced with Nd(NO3)3·6H2O to obtain a high entropy doped lithium cobalt oxide positive electrode material, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005Ti 0.0025 O2.

[0046] Example 8

[0047] The difference from Example 1 is that in step 2, the temperature is raised to 1000°C at 2°C / min and sintered for 20 hours to obtain a high entropy doped lithium cobalt oxide positive electrode material with a molecular formula of LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0048] Example 9

[0049] The difference from Example 1 is that in step 2, the temperature is raised to 950°C at 2°C / min and sintered for 12 hours to obtain a high entropy doped lithium cobalt oxide positive electrode material with a molecular formula of LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0050] Example 10

[0051] The difference from Example 1 is that in step 2, the temperature is raised to 1000°C at 2°C / min in an oxygen atmosphere and sintered for 12 hours to obtain a high entropy doped lithium cobalt oxide positive electrode material, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0052] Embodiment 11

[0053] The difference from Example 1 is that in step 2, the temperature is raised to 1000°C at 2°C / min and sintered for 18h in an air atmosphere to obtain a high entropy doped lithium cobalt oxide positive electrode material, whose molecular formula is LiCo 0.995 Mg 0.005 Al 0.005 Pr 0.005 Ti 0.0025 O2.

[0054] Comparative Example 1

[0055] 1. Add the weighed Li2CO3 and Co3O4 (the molar ratio of Li:Co is 1.05:1) into a ball mill and mill at 450 rpm for 12 hours to mix them evenly;

[0056] 2. Place the evenly ground mixed sample in a muffle furnace, heat it to 1000°C at 2°C / min and sinter it for 12 hours. After cooling, add it to an agate bowl and grind it again. Heat it to 900°C at 2°C / min and sinter it for 6 hours. Cool it to room temperature to obtain lithium cobalt oxide positive electrode material with the molecular formula LiCoO2.

[0057] The positive electrode material prepared in Examples 1-11 and Comparative Example 1 was added with polyvinylidene fluoride binder, acetylene black conductive agent and N-methylpyrrolidone cosolvent for homogenization, and the positive electrode material was coated on a metal sheet to form a positive electrode sheet. The positive electrode sheet was then assembled with a diaphragm, an electrolyte and a lithium sheet to form a battery structure. The assembled battery was connected to a charger and initially charged by constant current charging and constant voltage charging. After charging was completed, the battery was tested for capacity and cycle performance, and the test parameters were as follows: 4.6V DCR for the first time; 4.6V DCR cycle (0.1C in the first week, 1C for the rest), and the results are shown in Table 1:

[0058] Table 1 Electrochemical properties of the positive electrode materials assembled into batteries prepared in Examples 1-11 and Comparative Example 1

[0059]

[0060]

[0061] Table 1 shows the electrochemical performance of lithium-ion batteries assembled from high-entropy doped lithium cobalt oxide positive electrode materials prepared in Examples 1-11 and batteries assembled from lithium cobalt oxide positive electrode materials in Comparative Example 1. As can be seen from Table 1, the high-entropy doped lithium cobalt oxide positive electrode materials prepared in Examples 1-11 have higher charge and discharge capacity, first efficiency and capacity retention rate than Comparative Example 1 after being assembled into lithium-ion batteries. Among them, the high-entropy doped lithium cobalt oxide positive electrode materials prepared in Examples 1 and 2 achieve the best performance, indicating that the method successfully establishes a dual protection mechanism of the surface interface and the bulk phase, and simultaneously constructs a dual-site doping of the surface integrated structure and the bulk phase (Li site and transition metal site), which enhances the cycle stability and first coulombic efficiency of the LCO positive electrode material at 4.6V.

[0062] Figure 1 The XRD patterns of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the high-entropy doped lithium cobalt oxide positive electrode materials of Examples 1 and 2 do not show any impurity peaks, proving that Mg, Al, Ti, and Nd (Pr) are successfully doped into the positive electrode materials, indicating that trace high-entropy doping of Mg, Al, Ti, and Nd (Pr) will not affect the crystal structure of the material. Figure 2 The discharge specific capacity cycle of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1 under the conditions of 1C (200 mA / g) and 4.6V cut-off voltage. Figure 3 The first coulombic efficiency (referred to as the first efficiency in the figure) of the high entropy doped lithium cobalt oxide positive electrode material of Example 1-2 and the lithium cobalt oxide positive electrode material of Comparative Example 1 under the conditions of 1C (200 mA / g) and 4.6V cut-off voltage. Figure 2 and 3 It can be seen that the maximum value is 211.06mAhg at 3-4.6V and 1C. -1 , 100 cycles still have 173.97mAhg -1 And 82.43% capacity retention rate, 200 cycles still has 147.74mAhg -1 The discharge specific capacity and capacity retention rate of 70% indicate that the electrical performance of high-entropy doped lithium cobalt oxide positive electrode materials is greatly improved compared with LiCoO2.

[0063] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.

Claims

1. A high entropy doped lithium cobalt oxide positive electrode material, characterized in that: The molecular formula of the high entropy doped lithium cobalt oxide positive electrode material is LiCo (1-y) Mg x Al y Pr z Ti 0.0025 O2 or LiCo (1-y) Mg x Al y Nd z Ti 0.0025 O2, where 0.001≤x≤0.01, 0.001≤y≤0.01, 0.001≤z≤0.

01.

2. The method for preparing a high entropy doped lithium cobalt oxide positive electrode material according to claim 1, characterized in that: The following steps are involved: S1. A lithium compound, a cobalt compound, a titanium compound, a magnesium compound, an aluminum compound, a neodymium compound or a praseodymium compound is placed in a ball mill and ground to obtain a mixed powder; S2. The mixed powder is heated to 800-1200° C. in an atmosphere of air or oxygen and sintered. After cooling to room temperature, the mixed powder is heated to 800-1200° C. and sintered again to obtain high-entropy doped lithium cobalt oxide.

3. The method for preparing the high entropy doped lithium cobalt oxide positive electrode material according to claim 2, characterized in that: In step S1, the lithium compound is one or more of lithium hydroxide, lithium carbonate or lithium acetate; the cobalt compound is one or more of cobalt trioxide, cobalt sulfate or cobalt nitrate; the titanium compound is tetrabutyl titanate and / or titanium oxide; the magnesium compound is one or more of magnesium nitrate, magnesium oxide, magnesium sulfate or magnesium chloride; the aluminum compound is one or more of aluminum sulfate, aluminum oxide, aluminum acetate or aluminum fluoride; the neodymium compound is neodymium oxide and / or neodymium nitrate, and the praseodymium compound is praseodymium oxide and / or praseodymium nitrate.

4. The method for preparing the high entropy doped lithium cobalt oxide positive electrode material according to claim 2, characterized in that: The added amounts of the titanium compound, magnesium compound, aluminum compound, neodymium compound or praseodymium compound in step S1 are 0.1-1 mol% of the high entropy doped lithium cobalt oxide positive electrode material respectively.

5. The method for preparing the high entropy doped lithium cobalt oxide positive electrode material according to claim 2, characterized in that: The molar ratio of Li in the lithium compound and Co in the cobalt compound in step S1 is (1-x):(1-y), 0≤x≤0.1, 0≤y≤0.

1.

6. The method for preparing the high entropy doped lithium cobalt oxide positive electrode material according to claim 2, characterized in that: The grinding speed in step S1 is 400-1000 rpm, and the grinding time is 10-20 hours.

7. The method for preparing the high entropy doped lithium cobalt oxide positive electrode material according to claim 2, characterized in that: The heating rate in step S2 is 1-5°C / min, the first sintering time is 10-20h, and the second sintering time is 5-10h.

8. Use of the high entropy doped lithium cobalt oxide positive electrode material according to claim 1 in lithium ion batteries.

Citation Information

Cited By

  • Lithium cobalt oxide composite material, preparation method, positive plate and lithium ion battery

    CN121149182A

  • Preparation method for regulating and controlling particle entropy distribution of lithium cobalt oxide positive electrode material and high-voltage lithium ion battery

    CN121536973A